Bacterially-mediated weathering of crystalline and amorphous Cu-slags. (January 2016) - Potysz, Anna; Grybos, Malgorzata; Kierczak, Jakub; Guibaud, Gilles; Lens, Piet N.L.; van Hullebusch, Eric D.
Abstract: Two types of Cu-slags (CS: crystalline massive slag and GS: granulated amorphous slag) exhibiting a different chemical and mineral phase composition were compared with respect to their susceptibility to bacterial weathering using Pseudomonas aeruginosa (n° CIP 105094). Abiotic conditions e.g. sterile growth medium and ultrapure water were used for comparison. The experiments were extended up to 112 days with a systematic liquid phase renewal every 14 days. The results revealed significant release of elements in the bacterially mediated weathering experiments. Concentrations of elements (Si, Fe, Cu, Zn and Pb) in the biotic solutions were increased at least by 20% up to 99% compared to abiotic ones. From 3 to 77% of the leached elements were associated to the fraction >0.22 μm. Scanning electron microscope observations demonstrated greater weathering of mineral phases in biotic experiments than in abiotic ones which is in accordance with the solution chemistry exhibiting higher concentrations of elements leached in biotic set-ups. In the case of CS, glass and sulfides weathering was yet observed in abiotic experiment, whereas partial dissolution of fayalite (Fe2 SiO4 ) was solely affected by the presence of bacteria. GS having a higher bulk content of metallic elements was found to be more stable than sulfide-bearing CS, while its (GS) glass matrix was found to weather easier under biotic conditions. Highlights: Pseudomonas aeruginosa significantly enhance the release of elements from Cu-slags. Bacteria and/or associated metabolites assist as biosorbent ( e.g. Zn). Amorphous slag is more susceptible to bio-weathering. Metal carriers of crystalline slag are prone to dissolution. Fe-bearing fayalite is altered solely due to the presence of bacteria.